The Military History of the Soviet Union - Higham, R. author. aut Link
VIII, 328 p.
Keywords: This volume provides an introduction to the history of the Soviet armed forces from 1917 to 1991. The authors highlight the many facets of the Cold War, including the rise of the Soviet Navy after the Great Patriotic War and the collapse of the Soviet Union which marks its twentieth anniversary in 2011.